Rapid Carbon Formation from Spontaneous Reaction of Ferrocene and Liquid Bromine at Ambient Conditions - Chalmpes, Nikolaos; Tantis, Iosif; Bakandritsos, Aristides; Bourlinos, Athanasios B; Karakassides, Michael A; Gournis, Dimitrios (Nanomaterials (Basel, Switzerland), 2020)
Herein, we present an interesting route to carbon derived from ferrocene without pyrolysis. Specifically, the direct contact of the metallocene with liquid bromine at ambient conditions released rapidly and spontaneously carbon soot, the latter containing dense spheres, nanosheets, and hollow spheres. The derived carbon carried surface C-Br bonds that permitted postfunctionalization of the solid through nucleophilic substitution. For instance, treatment with diglycolamine led to covalent attachment of the amine onto the carbon surface, thus conferring aqueous dispersability to t he solid. The dispersed solid exhibited visible photoluminescence under UV irradiation as a result of surface passivation by the amine. Hence, the present method not only allowed a rapid and spontaneous carbon formation at ambient conditions, but also surface engineering of the particles to impart new properties (e.g., photoluminescence).
Keywords: carbon; bromine; ferrocene; ambient conditions; rapid synthesis